From gender bias to gender awareness in medical education - Verdonk, Petra; Benschop, Yvonne W. M.; de Haes, Hanneke C. J. M.; Lagro-Janssen, Toine L. M. (Advances in Health Sciences Education, 2009)
Gender is an essential determinant of health and illness. Gender awareness in doctors contributes to equity and equality in health and aims towards better health for men and women. Nevertheless, gender has largely been ignored in medicine. First, it is stated that medicine was ‘gender blind’ by not considering gender whenever relevant. Secondly, medicine is said to be ‘male biased’ because the largest body of knowledge on health and illness is about men and their health. Thirdly, gender role ideology negatively influences treatment and health outcomes. Finally, gender inequality has been overlooked as a determinant of health and illness. The uptake of gender issues in medical education brings about specific challenges for several reasons. For instance, the political-ideological connotations of gender issues create resistance especially in traditionalists in medical schools. Secondly, it is necessary to clarify which gender issues must be integrated in which domains. Also, some are interdisciplinary issues and as such more difficult to integrate. Finally, schools need assistance with implementation. The integration of psychosocial issues along with biomedical ones in clinical cases, the dissemination of literature and education material, staff education, and efforts towards structural embedding of gender in curricula are determining factors for successful implementation. Gender equity is not a spontaneous process. Medical education provides specific opportunities that may contribute to transformation for medical schools educate future doctors for future patients in future settings. Consequently, future benefits legitimize the integration of gender as a qualitative investment in medical education.
Keywords: approches et analyses; discipline; europe; formation des médecins; médecine; pays-bas; projet charge mentale; rapports sociaux de sexe; régions géographiques; santé; sciences; sexisme; stéréotypes de genre; systèmes d'oppressions; thématiques; éducation

Woman: An intimate geography - Angier, Natalie (Anchor Books, 2000)
Woman is a fascinating, fact-filled guide that covers everything from organs to orgasms, hormones to hysterectomies. With her characteristic clarity, insight, and sheer exuberance of language, bestselling author Natalie Angier cuts through the still-prevalent myths and misinformation surrounding the female body, that most enigmatic of evolutionary masterpieces. With a witty and assured narrative, and a reader-friendly dose of science, Woman is an essential and engaging resource for all time.
Keywords: amériques; approches et analyses; biologie; corps; cours; différence des sexes; discipline; fem1000; médecine; premier cycle; psychologie; rapports sociaux de sexe; régions géographiques; santé; sciences; sciences humaines; stéréotypes; thématiques; états-unis